PERAN BERAT MOLEKUL PROTEIN ENZIM EKSTRAKSELULER FUSARIUM OXYSPORUM FS.P. CUBENSE SEBAGAI FAKTOR VIRULENSI PADA TANAMAN PISANG - Ambar, Abdul Azis (Journal Galung Tropika, 2012)
The research aims to study the role of extracellular enzymes molecule wight on the virulence of Fusarium oxysporum f.sp. cubence (Foc). The study was conduvted in the glass house, laboratory of plant pathology. The isoletd used in this research are Bnt 1 and Bnt 2 from Yogyakarta, Btu 3 from Malang, Wsb 3 from Wonosobo, Lmp 3from Lampung and, Kjg 3 from Kalimantan. Banana cultivar ambon kuning is used as tested plant. Pathogenicity test is conducted by using hydroponic system. The plant roots are injured with a needle and then put into filled with sterile water. The suspension of Foc conodia is added in to plastic cup up to 106 spore/ml in concentration. Observation of symptom was conducted at 6 week by counting the score of necrotic symptom (RDI/Rhizome Discoloration Index) on banana cob which cut horizontally. Analysis extracelluler enzymes is done by using sodium dodecyl sulphate polycrylamide gel electrophoresis (SDS-PAGE). The result of pathogenicity test showed that the virulence of six isolates of Foc is not significantly different. Est of extracellular enzyme activity on six isolates of Foc showed that there is significant different between extracellular enzymes activity on isolates of Bnt 2, Wsb 3, Lmp 3, Kjg 3, and control but not for isolates of Bnt 1 and Btu 3. The six isolates have protein variation both amount and type that is probably related to its patogenisity. The result of SDS-PAGE showed that the six isolates of Foc have same protein pattern at 55,6 kDa. Protein pattern of Bnt 1, Bnt 2, Btu 3, Wsb 3, and Lmp 3 is laid on 42.84 kDa. Isolate of Bnt 2 has protein pattern at 36.5 kDa and Btu 3 has protein pattern at 20 kDa. The protein pattern that approaches to the pattern of polygalacturonase is Bnt 2 at 36.5 kDa molecule wight.